Las canciones infantiles como recurso didáctico y su incidencia en el desarrollo de la expresión corporal de los niños y niñas de primer año de educación general básica de las escuelas fiscales mixtas Manuel Isaac Encalada Zúñiga y Aurelio Prieto Muelas de la parroquia Buenavista, cantón Pasaje, periodo lectivo 2013-2014. - Saldaña Erraez, Mayra Maricela (2014)
The present research deals with the incidence that has the use of children's songs as didactic resources in the development of the corporal expression of the children of First year of General Basic education of the mixed tax schools Manuel Isaac Encalada Zuñiga and Aurelio Prieto Buenavista parish, being the corporal expression one of the fundamental axes for the full development of the students, that facilitates the social relations, individual, also allows the boy and the girl to express their feelings, emotions and interests discovering their possibilities and taking Awareness of their limitations.